The endocrinological aspects of Down's syndrome - A. V. Vitebskaya (Сеченовский вестник, 2014)
The article considers the role of the endocrinologist in the treatment of patients with Down syndrome. Particular attention is paid to the diagnosis and therapy, an integrated approach to the treatment of complex patients taking into account features of the disease.